Fresno County Bar Association Old-Timers Luncheon - Watkins, Howard::::::::: (1984)
Former Fresno County Bar Association President (1964) Max Hayden recounting story of attorney James V. Paige and his "fastest notary seal in the West" Hayden holding up Paige's notary seal and plaque with his holster that held the seal